One-dimensional van der Waals material InSeI with large band-gap for optoelectronic applications - Choi, Kyung Hwan; Cho, Sooheon; Jeong, Byung Joo; Lee, Bom; Jeon, Jiho; Kang, Jinsu; Zhang, Xiaojie; Oh, Hyung Suk; Lee, Jae Hyun; Yu, Hak Ki; Choi, Jae Young (Journal of Alloys and Compounds, 2022)
We experimentally demonstrate for the first time that the bulk InSeI crystals can be effectively delaminated by micromechanical exfoliation into a few nanometer-scale InSeI nanowires, due to the presence of weak van der Waals (vdWs) interaction within the crystal lattice. The exfoliated InSeI nanowires show one-dimensional (1D) bundle structure, and the work function of InSeI measured by Scanning Kelvin probe microscopy shows strong dependency on its thickness. The InSeI has a large bandgap corresponding to 2.12 eV, and when applied to a UV-detecting device, it was confirmed that the device with excellent sensitivity can be obtained, because there is little interference in the infrared and visible light regions. Based on these results, InSeI could be a excellent candidate as an additional 1D vdWs material for optoelectronics, including photodetectors or photovoltaic devices.
Keywords: Nanowires; One-dimensional van der Waals; Optical property; Scanning Kelvin probe microscopy; UV-detectors